EVALUASI PENGEMBANGAN PEGAWAI DI PEMERINTAHAN DAERAH (STUDI KASUS DI KOLAKA UTARA) - Said, Achmad Lamo (Departemen Ilmu Administrasi FISIP UNHAS, 2019)
This study aimed to find out and describe employee development in carrying out the main tasks and functions in the Education and Culture Office of North Kolaka Regency. This research is a qualitative descriptive technique through data reduction, data presentation, drawing conclusions, namely giving a comprehensive picture of the main problems discussed, especially those relating to employee development in carrying out the main tasks and functions of the North Kolaka District Education and Culture Office. The data collection techniques are direct observation, direct interviews. The results of the study show that employee training is carried out by sharing work orientation with regard to the ability, accuracy, and accuracy of employees in completing what is given by the leadership. Employee education is very concerned about attendance and attendance according to a set schedule so that it can optimize its main tasks and functions, as well as the provisions of working hours, have been carried out properly but there are still employees who are always out at work or personal matters. Employee development enhances the ability of employees to still rely on training invitations from external parties at the North Kolaka District Education and Culture Office and there are still employees whose placement is not in accordance with job competencies. Abstrak Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan tentang pembinaan pegawai dalam melaksanakan tugas pokok dan fungsi di Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka Utara. Penelitian ini merupakan penelitian dengan teknik deskriptif kualitatif melalui reduksi data, penyajian data, menarik kesimpulan yaitu memberikan gambaran secara menyeluruh tentang masalah pokok yang dibahas khususnya yang berkaitan dengan pembinaan pegawai dalam melaksanakan tugas pokok dan fungsi di Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka Utara. Adapun teknik pengumpulan data adalah observasi langsung, wawancara langsung. Hasil penelitian menunjukkan bahwa pelatihan pegawai dilakukan dengan pembagian orientasi kerja dengan memperhatikan kemampuan, kecermatan, dan ketepatan pegawai dalam menyelesaikan apa yang diberikan oleh pimpinan. Pendidikan pegawai sangat memperhatikan kehadiran dan hadir sesuai jadwal yang ditetapkan sehingga dapat mengoptimalkan tugas pokok dan fungsinya, begitu pula dengan ketetapan waktu jam kerja sudah dilaksanakan dengan baik namun masih ada pegawai yang selalu keluar dijam kerja atau ada urusan pribadi. Pengembangan pegawai peningkatan kemampuan pegawai masih mengandalkan undangan pelatihan dari pihak eksternal Dinas Pendidikan dan Kebudayaan Kabupaten Kolaka Utara serta masih ada pegawai yang penempatannya belum sesuai dengan kompetensi jabatan.